10TH JOINT CONFERENCE ON MATHEMATICS AND COMPUTER SCIENCE. ABSTRACTS - SOOS, Anna (Presa Universitară Clujeană, 2014)
The book contains the abstracts of 10th Joint Conference on Mathematics and Computer Science, hosted by the Faculty of Mathematics and Computer Science of the Babeș-Bolyai University, Cluj. The conference program, with four plenary talks and over 80 announced session talks, offered a great variety of excellent contributions in major areas of mathematics and computer science.